To evaluate the roles of the public library staff at the National Library Board, Singapore in the electronic environment. - Lim, Rachel Li Sa. (2008)
This study will evaluate the roles of the public library staff at NLB in the electronic environment with a view to identify how far the public library services have moved and how much farther are they from the expected roles of the 21st century public libraries.